A survey on preparatory english 1 undergraduates perceptual learning style preferences and their instructors teaching styles - Huong, Fei Fei (Faculty of Cognitive Sciences and Human Development., 2008)
This study aims to investigate the perceptual learning style preferences of undergraduates in Preparatory English I course in Semester I, Session 2007/2008 and their instructors' teaching styles. The objectives of the study are to investigate the undergraduates' learning styles and their instructors' teaching styles, as well as the relationship between the teaching and learning styles. Six types of learning/teaching styles were being investigated in this study, namely visual, tactile, auditory, kinesthetic, group and individual styles. 541 undergraduates' perceptual learning styles preference in terms of gender, races, and streams of study, and 24 instructors' teaching styles were investigated and the data were collected through questionnaires. The survey results showed that auditory learning style was the undergraduates' major learning styles. The statistical tests revealed that the undergraduates' preference on the learning styles was not influenced by their gender and streams of study. However, there was a significant difference in undergraduates' preference on tactile, auditory, kinesthetic and group learning styles based on races. The findings of the study revealed that kinesthetic and group learning styles were highly preferred by the instructors. Therefore, it suggested that there was no significant relationship between the teaching styles and learning styles. The issue of mismatch was found in the classrooms. The findings may imply that there is a need for the instructors and the undergraduates themselves to be more aware on the existence of differences in learning in order to achieve successful learning.